INTERACTIVE TEACHING METHODS: NEW OPPORTUNITIES IN THE TEACHING AND LEARNING PROCESS (FAN, TA’LIM, TEXNOLOGIYA VA ISHLAB CHIQARISH INTEGRATSIYASI ASOSIDA RIVOJLANISH ISTIQBOLLARI, 2025)
This article explores the role of interactive teaching methods in modern education, emphasizing their potential to enhance the teaching and learning process. It highlights how interactive approaches, including the use of technology like gamification, collaborative platforms, and virtual reality, can increase student engagement and foster deeper understanding. The article discusses the benefits of personalized learning, critical skill development, and immediate feedback, while also acknowledging the challenges teachers face, such as technology access and the need for professional development. Ultimately, the piece argues that interactive teaching is a crucial advancement in education, offering new opportunities for more dynamic, effective, and inclusive learning environments.